Study on effect of duration of mechanical ventilation on retinopathy of prematurity in low birth weight neonates admitted to neonatal intensive care unit - N., Madhu G.; H., Anil (International Journal of Contemporary Pediatrics, 2021)
Background: There has been an increase in morbidity in low birth weight infants, since the advancement in field of neonatology. Various resuscitation methods and life saving interventions are associated with adverse effects. One such intervention is mechanical ventilation and if prolonged, it is known to cause various morbidities like bronchopulmonary dysplasia, retinopathy of prematurity, vocal cord injury. In this study we are considering the effect of duration of ventilation on retinopathy of prematurity. Methods: This study is a prospective study, an observational study. The study was conducted in Kempegowda Institute of Medical Sciences, Bangalore. Total of 60 low birth weight infants (<2500gm) who were admitted to the Neonatal Intensive Care Unit (NICU) and were on mechanical ventilator support were included in the study. The study was conducted for a duration of 18 months, between January 2019 to June 2020. Results: Retinopathy of prematurity (ROP) was seen in 19 cases and was the most common complication associated with increasing duration of mechanical ventilation, which accounted for 48% of total complications, followed by abnormal otoacoustic emission (OAE) 17.95%, pneumothorax 10.26%, apnea 7.69%, pneumonia and bronchopulmonary dysplasia 5.13% and Hypoxic ischaemic encephalopathy (HIE) and seizures 2.46%. Conclusions: In this study, we were able to know the common complications involved in prolonged mechanical ventilation. This provides us to think about needs for measures to reduce the duration of mechanical ventilation and thereby reducing morbidities associated with it.